2009
DOI: 10.1515/shll-2009-1047
|View full text |Cite
|
Sign up to set email alerts
|

A Usage-Based Account of Syllable- and Word-Final /s/ Reduction in Four Dialects of Spanish

Abstract: Several linguistic factors have been shown to condition the reduction of syllableand word-final /s/ in Spanish (e.g. ¿Cómo estás tú? > ¿Cómo e [h]tá [ø] tú? 'How are you?'). These include word length (mono vs. polysyllabic words), the prosodic stress of the syllable in which syllable-or word-final /s/ occurs (stressed vs. unstressed), the position of /s/ within the word (internal vs. final), as well as the factor group shown to the have the greatest conditioning effect, the phonological context that follows s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
40
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 0 publications
3
40
0
1
Order By: Relevance
“…It should be noted that all predictor factors, not just frequency, will likely lose conditioning effect as a linguistic change nears completion. 9 Although the results of this paper concur with previous literature, and specifically Brown (2009b) with regards to Spanish, the finding that frequency plays no role in /s/ weakening in the Barranquilla data contradicts the results of FileMuriel (2009), a study that also analyzes /s/ in Barranquilla Spanish. However, several factors distinguish that study from the present one.…”
Section: Cali Versus Barranquillasupporting
confidence: 66%
See 2 more Smart Citations
“…It should be noted that all predictor factors, not just frequency, will likely lose conditioning effect as a linguistic change nears completion. 9 Although the results of this paper concur with previous literature, and specifically Brown (2009b) with regards to Spanish, the finding that frequency plays no role in /s/ weakening in the Barranquilla data contradicts the results of FileMuriel (2009), a study that also analyzes /s/ in Barranquilla Spanish. However, several factors distinguish that study from the present one.…”
Section: Cali Versus Barranquillasupporting
confidence: 66%
“…Several studies have shown that the preceding and following phonological contexts are two of the most influential factors in predicting the phonetic realization of /s/ in Spanish. Brown (2005) shows that the preceding context is the most influential factor in the prediction of syllable-initial /s/ realization while Brown (2009b) shows that the following context is most influential in the prediction of syllable-and word-final /s/ realization. Consequently, in a study such as this one, it is vitally important to statistically control for these two highly influential variables in order to accurately measure the relative influence of the two frequency measurements investigated here.…”
Section: Predictor Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…K. Brown & Brown 2012). For example, rates of [h] realization can be as high as 92% for speakers from Puerto Rico, and as low as 36% for speakers from speakers from Colombia; furthermore, for these and other documented varieties, rates differ for segments in medial compared to final position (E. K. Brown 2009). (Presumably, rates also differ from one word to the next but, to our knowledge, no study of Spanish has published the relevant statistics for individual lexical items; for statistics on variation in English, see Patterson & Connine 2001;Patterson, LoCasto & Connine 2003).…”
Section: Introductionmentioning
confidence: 99%
“…In the latter position, however, it occurs less frequently and is often sociolinguistically stigmatized (Narbona et al, 2003, p. 205). Several factors have been shown to favour a weakening of syllable-final /s/ in Spanish, such as its occurrence in unstressed syllables (e.g., Alba, 1990;File-Muriel & Brown, 2011), a fast speech rate (File-Muriel & Brown, 2011), high lexical frequency (e.g., Brown, 2009), and word-medial position preceding consonants (e.g., Alba, 1990;Momcilovic, 2009;Samper Padilla, 2011).…”
mentioning
confidence: 99%